Sukuk Linked Wakaf For MSME Develpoment - R. Melda Maesarach; Tri Mulato; Ahmad Rodoni (Universitas Muhammadiyah Jakarta, 2022)
The existing Sharia investment products are incorrect; the other is a state sukuk product. Aside from receiving returns on state sukuk, investors can also contribute to the country's development. Because the development of sukuk products is channeled to the actual sector, particularly for MSME (Micro, Small Maedium Enterprise) actors, Islamic financial institutions must play a role in carrying out the process of developing and aiding MSMEs. If many state sukuk products were previously allocated for infrastructure development, there needs to be an allocation for economic recovery through MSMEs under the current situations. The goal of this research is to assess the growth of state sukuk and the form of sukuk product development through state CWLS for the development of MSMEs. This is a qualitative study that examines the state sukuk market and the MSME sector. Secondary data was used, including information from the Ministry of Finance's Directorate General of Financing and Risk Management (DJPPR). The data analysis technique employed is descriptive qualitative, which depicts the evolution of state sukuk from 2019 to 2020, as well as forms of innovation for state sukuk goods designed specifically for MSMEs recovering from the covid-19 outbreak. PBS Auction Sukuk, PBS Private Placement Sukuk, SNI, SPN-S, Rite Sukuk (SR), and Savings Sukuk (ST) grew by 40.80% from 2019 to 2020, according to the findings of this study. Sukuk auctions at PBS increased by 39.59 percent, PBS Private Placement Sukuk increased by 214.39 percent, SR increased by 72.93 percent, and SNI Sukuk increased by 26.86 percent. In the meantime, SNI Sukuk fell by -30.01 percent, and ST fell by -35.76 percent. Providing business capital through Nazhir with a profit-sharing scheme, business assistance schemes, and maximizing the types of Waqf sukuk distributed to the productive sector are all schemes that can be implemented in developing MSMEs through the CWLS sukuk.